Autophagy Inhibitors Do Not Restore Peroxisomal Functions in Cells With the Most Common Peroxisome Biogenesis Defect - Klouwer, Femke C. C.; Falkenberg, Kim D.; Ofman, Rob; Koster, Janet; van Gent, Démi; Ferdinandusse, Sacha; Wanders, Ronald J. A.; Waterham, Hans R. (Frontiers in Cell and Developmental Biology, 2021)
Peroxisome biogenesis disorders within the Zellweger spectrum (PBD-ZSDs) are most frequently associated with the c.2528G>A (p.G843D) mutation in the PEX1 gene (PEX1-G843D), which results in impaired import of peroxisomal matrix proteins and, consequently, defective peroxisomal functions. A recent study suggested that treatment with autophagy inhibitors, in particular hydroxychloroquine, would be a potential therapeutic option for PBD-ZSD patients carrying the PEX1-G843D mutation. Here, we studied whether autophagy inhibition by chloroquine, hydroxychloroquine and 3-methyladenine indeed can improve peroxisomal functions in four different cell types with the PEX1-G843D mutation, including primary patient cells. Furthermore, we studied whether autophagy inhibition may be the mechanism underlying the previously reported improvement of peroxisomal functions by L-arginine in PEX1-G843D cells. In contrast to L-arginine, we observed no improvement but a worsening of peroxisomal metabolic functions and peroxisomal matrix protein import by the autophagy inhibitors, while genetic knock-down of ATG5 and NBR1 in primary patient cells resulted in only a minimal improvement. Our results do not support the use of autophagy inhibitors as putative treatment for PBD-ZSD patients, whereas L-arginine remains a therapeutically promising compound.